CHARACTER EXCELLENCE COACHING UNTUK PERSONAL GROWTH INITIATIVE MAHASISWA DALAM MENULIS KARYA ILMIAH - Putri, Dian Febriany; Bantam, Dian Juliarti (Universitas Islam Indonesia, 2024)
Writing activities among higher education students are one of the primary activities. The declining interest and initiative in writing among students contrasts with the skills needed in the workforce. One way to enhance students' initiative in writing scientific papers is through coaching activities. This study aims to prove the effectiveness of Character Excellence Coaching in increasing Personal Growth Initiative (PGI) among students in writing scientific papers. The design used is one-group pretest and posttest design. The respondents were 7 students from Faculty X who are in their 5th and 7th semesters. The measurement tool used was the Personal Growth Initiative Scale-II. Wilcoxon test analysis showed a decrease in personal growth initiative scores after the intervention with a mean difference of 0.429 and a p-value of 0.850 (>0.05). This means that the Character Excellence Coaching intervention was not significantly effective in increasing the personal growth initiative among students.